Upaya Mewujudkan “Agent Of Democracy” Melalui Pendidikan Politik Kebangsaan Pada Karangtaruna Tunas Harapan Desa Tonggara Kecamatan Kedungbanteng - Prasetya Putra Nugraha; Nofan Nurkhafid Azmi; Himawan Ardhi Ristanto (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Community service activity themed “Efforts to Foster Agents of Democracy Through National Political Education for the Karangtaruna Tunas Harapan in Tonggara Village, Kedungbanteng Distrrict” has been implemented well. This activity aims to improve understading of national political education among the members of the Karangtaruna Tunas Harapan, and establishing it as an agent for upholder of democracy. Based on the results of the activities, the impelementation of community service focuses on three main aspects, that is improvement of literacy and political education awareness, leadership training, and innovation in program development. The conclusions indicate the impelementation of the program successfully addressed the main challenges faced by the partners. Through outreach activities, political education, leadership training, and organizational governance, as well as assistance to youth organization members regarding the importance of understanding political education in fostering agents of democracy.